Sesquiterpenoids from the Whole Plants of Chloranthus holostegius and Their Anti‐inflammatory Activities. Issue 5 (21st April 2021) - Zhan, Zhao‐Chun; Wu, Zhong‐Nan; Tang, Qing; Li, Can‐Jie; Wang, Wen‐Zhi; Zhang, Ji‐Hui; Zhuo, Xue‐Fang; Zhang, Yu‐Bo; Wang, Guo‐Cai; Li, Yao‐Lan
Main observation and conclusion: Five new sesquiterpenoids (1—5), chloranholides A—E, along with three known compounds (6—8), were isolated from the whole plants of Chloranthus holostegius . Their structures were elucidated using the spectroscopic methods (IR, UV, HR‐ESI‐MS, 1D and 2D NMR), and their absolute configurations were determined by the X‐ray crystallography and ECD calculation. Compounds 1—8 were evaluated for their anti‐inflammatory effects on LPS‐induced RAW 264.7 macrophage cells. Especially, compound 4 exhibited the most significant anti‐inflammatory activity with the secretion levels of TNF‐α and IL‐6 at 15.52% and 5.98%, respectively, better than that of dexamethasone. Abstract :